The machineries of user knowledge production. (January 2018) - Oygür, Işıl
Abstract : A multiple case study was conducted to investigate the machineries of designers' user knowledge production at six design consultancies in the Northwestern USA in domains of architecture, industrial design, and interaction design. Karin Knorr Cetina's theory of epistemic cultures was utilised as the theoretical lens. The findings indicate that the user is not a given; instead, the user is a constructed phenomenon in design. The design process is characterised by the deconstruction and reconstruction of the user information and of experiential information, implemented to meet the epistemic needs of designers. User representations are used as the liminal knowledge. Designers manipulated this knowledge in order to narrow down the artefact to be designed. Highlights: User, constructed by designers, is the liminal knowledge in design process. Epistemic objects on user and experiential knowledge are significant for user knowledge construction. User knowledge construction is characterized by deconstruction and reconstruction processes. Designers manipulated their liminal knowledge on user in order to narrow down the artefact to be designed.